ANALYSIS OF INDIHOME WIRELESS FIDELITY (WI-FI) SERVICES BETWEEN MALE AND FEMALE CUSTOMER IN MANADO - Muljono, Wulan .; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Technology has dramatically changed people behaviors. The role of technology continues its long-standing expansion and becomes increasingly important to everyone. Peoples rely on the Internet to search for travel information, communicate with friends and sharing status updates on social media (Ahmed, 1991). Indihome is one of PT. Telkom service product in the form of communication and data service package. Indihome began to be developed in 2015 and was previously named Speedy. The aim of this study is to analyze the difference perception of Indihome Wi-Fi services to its customer divided by male and female group in Manado based on perceived ease of use, perceived usefulness, and speed and brand image. This research is a quantitative research and uses independent sample t-test. The sample size of this research is 100 customer of Indihome (50 male and 50 female) who have already experienced Indihome Wi-Fi services. The results showed that there is no significant difference in Indihome Wi-Fi services based on perceived ease of use, perceived usefulness, and brand image. While for the variable of speed there is a significant difference. The recommendatio which are Indihome should open more access to it is services to the other part of Indonesia, Indihome should take care of it is product regarding router, Indihome should more pay attention to its speed of service in order to fulfill it is customer needs and wants. Keywords: wireless fidelity, wi-fi, comparative analysis, indihome, perceived ease of use, perceived usefulness, speed, brand                    image.